Analisis Faktor-faktor Yang Mempengaruhi Niat Komplain: Studi Pada Konsumen Goeboex Coffee Yogyakarta - , Dwi Kartika Sari, Dra. Yulia Arisnani Widyaningsih, M.B.A., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Complaining behavior intentions can be defined as the intention of the consumer who were disappointed and made a complaint to the company and is the result (outcome) immediately prior to the formation of attitudes from the perspective of behavioral responses. The company is expected to identify the shape of consumer dissatisfaction with analyzing the factors that drive the intention complaint. Previous research suggests several factors that affect the complaint intention namely attitudes towards complaints, the level of information, the level of dissatisfaction, the importance of the situation, and the possibility of successful complaints. Adopted from a previous study by Blascoet et. al, (2010) which aims to find the most influential factor on complaint intentions. Object of research is one of the companies engaged in service (coffee shop). Methods of collecting data were the distribution of questionnaires to 150 respondents. The results of this study indicate that attitudes towards complaints have a significant effect on the level of dissatisfaction with the intention of complaints, while other factors had no effect. Researcher also contributed a few suggestions for the managerial improvement of those findings.